Analisis penggunaan media buku cerita bergambar pada pembelajaran bahasa indonesia di kelas II sd - Nuralifah, Rosi; Rukayah, Rukayah; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2022)
The purpose of this study was to describe the use of picture story books inIndonesian language learning in class II SD N 1 Dawuhan Purbalingga. This type of researchis a qualitative research. Subject selection technique using purposive sampling technique. Theresearch subjects were class II students and class II teachers at SD N 1 DawuhanPurbalingga. Sources of data come from students and teachers of class II. Data collectiontechniques using interviews, observation and documentation. Data validity uses triangulationtechniques. Data analysis used Miles and Huberman analysis techniques. The researchprocedure carried out is to reduce data, present data, and draw conclusions. Aspects of the useof picture story media include the relevance of media use, ease of use, the usefulness of media,the ability of teachers to use media, and the availability of media. The results showed thatpicture story books are relevant with basic competencies, objectives, and materials, easy touse, useful, teachers are able to use media, and are available. From the results of the study itwas concluded that the learning media for picture books is an appropriate learning media forIndonesian language learning in class II SD N I Dawuhan Purbalingga. The theoreticalimplication of this research is to find out the usefulness of using picture story books inIndonesian language learning.